2003
DOI: 10.1078/0944-5013-00187
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere microflora of plants used for the phytoremediation of bitumen-contaminated soil

Abstract: The microbial communities and their degradative potential in rhizospheres of alfalfa (Medicago sativa) and reed (Phragmites australis) and in unplanted soil in response to bitumen contamination of soil were studied in pot experiments. According to the results of fluorescence microscopy, over a period of 27 months, bitumen contamination of soil reduced the total number of microorganisms more significantly (by 75%) in unplanted than in rhizosphere soil (by 42% and 7% for reed and alfalfa, respectively) and had v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 23 publications
0
21
0
4
Order By: Relevance
“…The microorganism also influences a number of processes associated with the metabolism of biogenic elements, like sulphur [44], which may also explain why the biopreparation caused the rate of decrease to almost double in the content of sulphur in the control treatment. Dimitrov and Mitov [45] found that the content of nutrients in plants growing on soils contaminated with petroleum-derived substances depends much on the species of plant.…”
Section: Resultsmentioning
confidence: 99%
“…The microorganism also influences a number of processes associated with the metabolism of biogenic elements, like sulphur [44], which may also explain why the biopreparation caused the rate of decrease to almost double in the content of sulphur in the control treatment. Dimitrov and Mitov [45] found that the content of nutrients in plants growing on soils contaminated with petroleum-derived substances depends much on the species of plant.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated increased degradation of petroleum hydrocarbons (such as phenanthrene, benzo[a]pyrene, benzo[a]anthracene, chrysene, hexadecane, benzene, toluene etc.) as a result of modified microbial activity in the rhizosphere of grasses and legumes (Nichols et al 1997;Miya and Firestone 2001;Corgié et al 2003;Muratova et al 2003;Phillips et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although, crude oil spills in soil affect plants adversely by creating conditions which make essential nutrients like nitrogen and oxygen used for plant growth unavailable to them [4], plant roots can act as a substitute for the tilling of soil to incorporate additives (nutrients) and to improve aeration [6,43]. Therefore, plants with well-developed root system such as popular, willow [44] and reed (Phragmites australies), possessing specialized root vessels, aerenchyma which can release oxygen into the rhizosphere in deep soil layer [44,45] are preferentially selected for rhizoremediation.…”
Section: Discussionmentioning
confidence: 99%